Performance Measurement Analysis Based on The Balanced Scorecard at The Private Hospital in Boyolali, Indonesia - Mushhaf, Muhammad Dhiyaul; Kuswati, Rini; Ichsan, Burhannudin (Universitas Muhammadiyah Yogyakarta, 2024)
Hospitals must contend with the fierce competition in the rapidly expanding healthcare business. Hospitals, particularly private ones, operate in a highly competitive health service business. Therefore, hospitals must engage in performance assessment in order to enhance many facets of their performance. This study aims to assess the efficiency of the private hospital in Boyolali, Indonesia, by employing the Balanced Scorecard method. Measurement was conducted utilizing four distinct perspectives: money, customers, internal company processes, and learning and growth. The study involved collecting primary and secondary data over four years, specifically from 2020 to 2023. Comparative analysis was employed to assess the hospital's performance throughout different periods and compare it to pre-established targets. Subsequently, a score was assigned based on the findings. The findings indicated a total score of 0.52, signifying that the overall performance evaluation results of this study are classified as satisfactory. It is necessary to oversee hospital investments, enhance marketing efforts, train workers to deliver exceptional care, and offer awards based on success.